Analisis Kelayakan Toko Karangan Bunga Soemardjan di Salatiga - Diana Nafaani; Gloria Yunannike; Adella Rahmawati; Jihan Safitri; Najwa Rahmawati D; Brian Area Saputra (Jurnal Kewirausahaan Cerdas dan Digital, 2026)
This study aims to analyze the feasibility level of the Soemardjan Flower Shop, a micro, small, and medium enterprise (MSME) engaged in florist services and located in Salatiga City. The feasibility analysis was conducted by considering the following six aspects: market and marketing aspects, technical and technological aspects, environmental aspects, legal aspects, management human resources aspects, and financial aspects. This study applies a qualitative descriptive method with a case study approach. Data collection techniques were carried out by observing, interviewing directly, recording related documents, and analyzing existing financial information. The study shows that the Soemardjan Flower Shop has a target market, a marketing strategy that utilizes digital media, an operational system that supports product quality, good environmental management, adequate business legality, and effective human resource management. Financial analysis shows that the business has succeeded in generating profits and meeting investment feasibility standards. Thus, the Soemardjan Flower Shop is considered feasible to be managed and developed further, and has the ability to maintain business continuity amidst the tight competition in the florist business. This research is hoped to help business owners come up with smarter and more sustainable ways to grow their businesses.